Carers, Care Homes and the British Media - Grist, Hannah. author. aut Link
XI, 112 p.
Keywords: This book focuses on the relationship between the media and those who work as paid care assistants in care homes in Britain. It explores this relationship in terms of the contemporary cultural and personal understandings of care work and care homes that have developed as the role has emerged as increasingly socially and economically significant in society. Three strands of analysis are integrated: an examination of the representations of paid care workers in the British media; the experiences of current and former care workers; and the autoethnographic reflections of the authors who have experiences of working as care assistants. The book offers a rich contextual and experiential account of the responsibilities, challenges, and emotions of care work in British society. Grist and Jennings make a case for the need to better value and more accurately represent care work in contemporary media accounts.